Box Wing Flight Dynamics in the Stage of Conceptual Aircraft Design - Ricardo Caja Calleja and Dieter Scholz (Deutsche Gesellschaft für Luft- und Raumfahrt - Lilienthal-Oberth e.V., 2012)
Different computational methods are available to evaluate the flying qualities of an aircraft in the stage of conceptual design. However, due to the unconventional configuration of the box wing aircraft, compatibility issues have been encountered with different software, the majority of which appear due to the influence of the second main wing. The independent use of different modules within CEASIOM (Computerized Environment for Aircraft Synthesis and Integrated Optimization Methods) has proved to be a feasible option. The aerodynamic coefficients and derivatives are calculated with Tornado, a vortex-lattice method (VLM) implemented in MATLAB. The SDSA (Simulation and Dynamic Stability Analysis) module of CEASIOM, allows for the determination of the aircraft dynamic modes and the evaluation of the flying qualities based on MIL-F-8785C Specifications. An interface between Tornado and SDSA is programmed by means of MATLAB scripts that read the output data of Tornado, and build the appropriate input files for SDSA. The dynamic modes are also determined and evaluated by hand methods for cruise conditions, in order to compare the results with those obtained with SDSA. The flying qualities of the box wing aircraft are Level 1 for most of the dynamic modes, although the Short Period and Roll Subsidence modes present Level 2 and Level 3, respectively. However, the numerical values show that such modes are close to Level 1 and Level 2, respectively. The overall results can be considered relatively good for a first analysis, and important changes in the design are not needed. The handling qualities have also been evaluated, with the help of a Flight Dynamics Model (FDM) defined with JSBSim and integrated in the visual flight simulator FlightGear. The pilot’s rating based on the Cooper-Harper rating scale is Level 1, 3 and 5 for cruise, take-off and landing conditions, respectively.
Keywords: box wing aircraft; flight dynamics